Prebiotics and their activity for the handling of diabetes: Literature review - Muhammad Shahazad Manzoor; Zia Ul Mustafa (Journal of Food Science and Nutrition Therapy - Peertechz Publications, 2019)
Prebiotics are non-digestible substance that provides a positive physiological effect by selectively stimulating the growth or action of a limited number of indigenous bacteria in the host. Form previous decade there is increase in public interest and demand for the development of new product and prebiotics formula to improve quality of life. Prebiotics are also used to treat type 2 diabetes by activation of receptors and microorganism recognition in the intestinal lumen. Assumed as pivotal role for treatment of metabolic disorders including major potential for intestinal microfl ora perspective. Also result in improvement of insulin sensitivity and reduction of autoimmune response. However, further researches are required to clarify whether the administration of probiotics can be profi ciently used for the prevention and treatment of type 2 diabetes.